2015
DOI: 10.3390/ijms160716440
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mammalian Target of Rapamycin Complex 1 (mTORC1) Downregulates ELOVL1 Gene Expression and Fatty Acid Synthesis in Goat Fetal Fibroblasts

Abstract: Elongation of very-long-chain fatty acids 1 (ELOVL1) is a ubiquitously expressed gene that belongs to the ELOVL family and regulates the synthesis of very-long-chain fatty acids (VLCFAs) and sphingolipids, from yeast to mammals. Mammalian target of rapamycin complex 1 (mTORC1) is a central regulator of cell metabolism and is associated with fatty acids synthesis. In this study, we cloned the cDNA that encodes Cashmere goat (Capra hircus) ELOVL1 (GenBank Accession number KF549985) and investigated its expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…ELOVL1 , a widely expressed gene in tissues from the ELOVL family, encoded the fatty acid elongase to produce C20–C28 fatty acids. In this study, ELOVL1 was observably upregulated in chicken jejuna from LPC-treated groups, consistent with the report that ELOVL1 regulated the very-long-chain fatty acid and sphingolipids synthesis, and was closely associated with the intestinal barrier function ( 22 , 23 ). ELOVL1 expression induced by inhibiting mTOR1 decreased fatty acids synthesis ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ELOVL1 , a widely expressed gene in tissues from the ELOVL family, encoded the fatty acid elongase to produce C20–C28 fatty acids. In this study, ELOVL1 was observably upregulated in chicken jejuna from LPC-treated groups, consistent with the report that ELOVL1 regulated the very-long-chain fatty acid and sphingolipids synthesis, and was closely associated with the intestinal barrier function ( 22 , 23 ). ELOVL1 expression induced by inhibiting mTOR1 decreased fatty acids synthesis ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, ELOVL1 was observably upregulated in chicken jejuna from LPC-treated groups, consistent with the report that ELOVL1 regulated the very-long-chain fatty acid and sphingolipids synthesis, and was closely associated with the intestinal barrier function ( 22 , 23 ). ELOVL1 expression induced by inhibiting mTOR1 decreased fatty acids synthesis ( 22 , 23 ). A previous study in mice indicated that ELOVL1 knockout induced the defects in the epidermal barrier and the death after birth.…”
Section: Discussionsupporting
confidence: 92%
“…The analysis of ELOVL1 homologues from different organisms showed that p.Ser165 is highly conserved being present in all the analysed species (n=80, figure 3D). The p.Ser165Phe mutation is located in the region that may undergo myristoylation7 (figure 3D), although experimental data are necessary to verify this prediction.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that lipid synthesis and myelin formation is under the control of mTORC1 signaling [157,158,159]. It is particularly noteworthy here that Elovl1 expression is downregulated upon inhibition of mTORC1, and the medium-chain fatty acid availability acts via mTORC1 signaling to trigger Elovl5 and Elovl6 expression [160,161,162,163]. Given that ataxin-2 orthologs in yeast, nematodes, and mice were shown to play a conserved role as inhibitors of mTORC1 signaling and growth [36,48,164,165,166], the broad repression of Elovl1/4/5/6 in cerebellum and spinal cord as well as the repression of Elovl2/7 in cerebellum may be a very sensitive and specific reflection of this ancient control of ATXN2 over lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%